Analysis of accounting treatment of corporate social responsibility (CSR) reporting - Ayu Edelyn Putri Cantika (ARKA INSTITUTE, 2022)
This study aims to determine the accounting treatment of corporate social responsibility reporting at PT. Madani National Capital (Persero) Sukabumi Branch and whether PT. Permodalan Nasional Madani (Persero) Sukabumi branch presents a report on social responsibility outside the main financial report as stated in PSAK No. 1 Paragraph 12 Revised 2009. This study uses a qualitative approach where the researcher analyzes how the accounting treatment of corporate social responsibility reporting in one of the state-owned enterprises. This research is in accordance with the research focus, where researchers expect to be able to obtain a clear and in-depth picture of the accounting treatment and reporting of corporate social responsibility. The results of the study state that the accounting treatment of CSR is recognized as an expense. The recognition of CSR as a burden by PT. National Capital Madani (Persero) so that the amount of the burden is measured based on the number of costs or funds issued by the company when the transaction or activity is carried out. In this case, the costs incurred during CSR activities.